A Analysis of the Application of Sunk Costs and Relevant Costs in Advertising Cost Decision-Making at CV Lifan Jaya: Analisis Penerapan Sunk Cost Dalam Pengambilan Keputusan Penggantian Biaya Iklan Pada CV Lifan Jaya - Lala, Paskalina; Mawikere, Lidia M.; Mintalangi, Syermi S.E (Universitas Sam Ratulangi, 2026)
This study aims to analyze the application of sunk costs and relevant costs in decision-making related to advertising expenses at CV Lifan Jaya. Data were collected through interviews and documentation of the company’s promotional activities. The results show that the annual replacement of the store signboard is classified as a sunk cost because it is routine, unavoidable, and does not affect future promotional decisions. Relevant costs at CV Lifan Jaya consist of expenses that may create new outlays, such as brochure printing and digital information optimization through Google Business Profile. The company does not incur costs for social media promotion, content creation, or paid digital campaigns; therefore, these components are not considered relevant costs. Based on the analysis, appropriate promotional decisions should focus on expenditures that provide direct marketing benefits and exclude previously incurred costs from consideration. Keywords : sunk cost, relevant cost, advertising cost, decision-making, CV Lifan Jaya.